2018
DOI: 10.1002/suco.201700248
|View full text |Cite
|
Sign up to set email alerts
|

A review of literature and code formulations for cracking in R/C members

Abstract: Cracking in R/C members is a complex phenomenon characterized by high scattering, mainly affected by concrete in tensile zone. The aim of this paper is to evaluate the effectiveness of formulas for crack width prediction developed in last decades. First, an historical review of available literature models is presented and discussed. Second, the progress and missteps, which have characterized the development of international code provisions, are shown. Finally, a comprehensive comparison between predicted crack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 20 publications
(26 reference statements)
1
26
0
1
Order By: Relevance
“…This high variation is indicative of the random nature of crack mechanisms and the resulting difficulties in modeling their behavior. The means and CoV's, as given in Table , for model uncertainty of EN 1992 and MC 2010 are comparable to those obtained by Lapi et al using maximum crack widths. Although there is some overlap in the large dataset used by Lapi et al (namely, Clark 1956 and Hognestad 1962) and that compiled for this study (Table ), the sources are largely independent, validating the short‐term flexure model uncertainty values obtained in this study.…”
Section: Results Of Model Uncertainty Quantificationsupporting
confidence: 82%
See 2 more Smart Citations
“…This high variation is indicative of the random nature of crack mechanisms and the resulting difficulties in modeling their behavior. The means and CoV's, as given in Table , for model uncertainty of EN 1992 and MC 2010 are comparable to those obtained by Lapi et al using maximum crack widths. Although there is some overlap in the large dataset used by Lapi et al (namely, Clark 1956 and Hognestad 1962) and that compiled for this study (Table ), the sources are largely independent, validating the short‐term flexure model uncertainty values obtained in this study.…”
Section: Results Of Model Uncertainty Quantificationsupporting
confidence: 82%
“…In the design of structures such as LRS, the stabilized cracking phase is assumed to have been reached. The predicted maximum crack width corresponds to a 5% probability of exceedance by design code formulations, which may not probabilistically match the measured maximum crack width, thus contributing to model uncertainty.…”
Section: Quantification Of Crack Model Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…Oh and Kang (1987) suggested a semi-empirical equation, where crack spacing has been related to reinforcement axial strain and bar diameter. Lapi, Orlando, and Spinelli (2018) have carried out an exhaustive review on code formulations for cracking in concrete which revealed that various linear functions with c, s (reinforcing bar spacing) and φ/ρ ef as key independent variables were exceedingly dominant in most international codes. The comprehensive review of cracking equations builds on the previous work conducted by Borosnyói and Balázs (2005).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, cracking control relies on the proper calculation of steel stresses upon cracking, as well as on appropriate evaluation of crack widths. The code formulations to perform such calculations have evolved over time (Knoppik et al 2019;Lapi et al 2018), and there is an ongoing effort to develop improved design rules (Caldentey et al 2018). Two important open questions can be identified, which need to be addressed by new calculation methods.…”
Section: Introductionmentioning
confidence: 99%